Nursing Care Analysis in Children with Down Syndrome and the Application of Puzzle Play Therapy - Zalva Khoirunisa, Nisrina; Yekti Widadi, Sri (CV. Literasi Publikasi Indonesia, 2024)
Down Syndrome is a condition characterized by physical and mental developmental delay caused by chromosomal abnormalities during cell division. One of the common complications in children with Down Syndrome is developmental disorders, including delays in motor skills and cognitive development. Non-pharmacological treatments, such as puzzle play therapy, can be used to enhance development. Puzzle play therapy is considered a beneficial intervention to improve fine motor skills and cognitive functions in children with Down Syndrome. This case study aims to provide an overview of the application of puzzle play therapy as a nursing intervention in children with Down Syndrome, focusing on addressing developmental disorders, particularly in fine motor skills. A descriptive case study design was employed, involving anamnesis, observation, physical examination, and analysis of nursing care based on evidence-based practice (EBP). The participant in this study was a child with Down Syndrome who was administered puzzle play therapy. The study found that puzzle play therapy effectively addressed developmental issues in a child with Down Syndrome. After the therapy, there was an improvement in the child’s fine motor skills, which indicates the success of puzzle play therapy as an intervention for developmental disorders in children with Down Syndrome. Puzzle play therapy can be successfully implemented in nursing care for children with Down Syndrome, particularly in improving fine motor skills and promoting cognitive development. It has been empirically proven to be an effective intervention for enhancing development in children with Down Syndrome.